2013
DOI: 10.1371/journal.pone.0066397
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Heparin Relieves Experimental Colitis in Mice by Downregulating IL-1β and Inhibiting Syndecan-1 Shedding in the Intestinal Mucosa

Abstract: Low molecular weight heparin (LMWH) exhibits anti-inflammatory properties, but its effect on inflammation in colitis remains unclear. This study aimed to evaluate the therapeutic effects of LMWH on dextran sulfate sodium (DSS)-induced colitis in mice, in which acute colitis progresses to chronic colitis, and to explore the potential mechanism involved in this process. C57BL/6 mice were randomly divided into control, DSS, and DSS plus LMWH groups (n = 18). Disease activity was scored by a disease activity index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
2
19
0
1
Order By: Relevance
“…Repeated oral administration of DSS-supplemented water to mice is a reliable model of chronic bowel inflammation (particularly, ulcerative colitis), recapitulating characteristic changes in the colon observed in human disease [38]. Single administration of DSS causes an acute inflammation in the colon [39], and we and others have previously shown that expression of Sdc1 is decreased in the DSS model and that Sdc1 deficiency results in an exacerbated acute inflammatory response [20,25,26,27]. When 2–3 cycles of DSS administration are applied, acute inflammation is followed by chronic colitis [39,40,41].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Repeated oral administration of DSS-supplemented water to mice is a reliable model of chronic bowel inflammation (particularly, ulcerative colitis), recapitulating characteristic changes in the colon observed in human disease [38]. Single administration of DSS causes an acute inflammation in the colon [39], and we and others have previously shown that expression of Sdc1 is decreased in the DSS model and that Sdc1 deficiency results in an exacerbated acute inflammatory response [20,25,26,27]. When 2–3 cycles of DSS administration are applied, acute inflammation is followed by chronic colitis [39,40,41].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, loss of Sdc1 expression is a characteristic feature of IBD both in experimental [20,25,26] and clinical [22,23,24] settings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, binding of chemokines to heparins decreases their ability to activate their receptors, thus decreasing their proinflammatory effects (29). Finally, heparin downregulates IL-1b and inhibits syndecan-1 shedding in the intestinal mucosa in an experimental model of colitis in mice (53). Interestingly, early heparin treatment or late urokinase treatment prevents lung fibrosis in response to bleomycin (18).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pulmonary inflammation can cause local disturbances in fibrin turnover whereas increased intra-alveolar fibrin deposition with decreased breakdown may induce inflammation (44). Given this tight cross talk between coagulation and inflammation, the administration of an agent (such as heparin) that has both anti-coagulant as well as anti-inflammatory properties (53) may reduce the disturbance in pulmonary coagulopathy and inflammation, thereby ameliorating the clinical course of ALI. Aerosolized heparin has been shown to be effective in patients with ALI, making this agent a candidate for clinical use in patients with Cl 2 -induced lung injury (11,19,20,49).…”
mentioning
confidence: 99%